Effects of gender, education, contact with older adults and health-related jobs on memory control beliefs across the lifespan - Marta Nieto; Rigoberto López; Laura Ros; José Miguel Latorre (Scientific Reports)
Abstract This work sheds light on which of the commonly studied variables explain presence of negative beliefs about memory in a sample of 1,673 participants (range: 12–96 years), using the Memory Controllability Inventory (MCI) and the Aging Concern Scales (ACS). A factor analysis of the MCI and ACS revealed a five-factor structure. Of these five, three presented adequate reliability indices: memory improvement, present ability and Alzheimer’s likelihood. The results showed that there are generational differences in the relationship of these factors to variables such as gender, educational level and the quality and frequency of contact with the elderly, with the frequency of contact with older people being one of the variables most associated with the three MCI and ACS factors, especially in the younger age groups. This work shows the importance of positive contact with older people in generating positive memory control beliefs. Finally, we discuss the importance of positive beliefs in clinical care for older adults.